Factors limiting the potential range expansion of lodgepole pine in Interior Alaska - Walker, Xanthe J.; Hart, Sarah; Hansen, Winslow D.; Jean, Mélanie; Brown, Carissa D.; Stuart Chapin, F.; Hewitt, Rebecca; Hollingsworth, Teresa N.; Mack, Michelle C.; Johnstone, Jill F. (Ecological applications, 2024)
Understanding the factors influencing species range limits is increasingly crucial in anticipating migrations due to human‐caused climate change. In the boreal biome, ongoing climate change and the associated increases in the rate, size, and severity of disturbances may alter the distributions of boreal tree species. Notably, Interior Alaska lacks native pine, a biogeographical anomaly that carries implications for ecosystem structure and function. The current range of lodgepole pine (Pinus contorta var. latifolia) in the adjacent Yukon Territory may expand into Interior Alaska, particularly with human assistance. Evaluating the potential for pine expansion in Alaska requires testing constraints on range limits such as dispersal limitations, environmental tolerance limits, and positive or negative biotic interactions. In this study, we used field experiments with pine seeds and transplanted seedlings, complemented by model simulations, to assess the abiotic and biotic factors influencing lodgepole pine seedling establishment and growth after fire in Interior Alaska. We found that pine could successfully recruit, survive, grow, and reproduce across our broadly distributed network of experimental sites. Our results show that both mammalian herbivory and competition from native tree species are unlikely to constrain pine growth and that environmental conditions commonly found in Interior Alaska fall well within the tolerance limits for pine. If dispersal constraints are released, lodgepole pine could have a geographically expansive range in Alaska, and once established, its growth is sufficient to support pine‐dominated stands. Given the impacts of lodgepole pine on ecosystem processes such as increases in timber production, carbon sequestration, landscape flammability, and reduced forage quality, natural or human‐assisted migration of this species is likely to substantially alter responses of Alaskan forest ecosystems to climate change.